Stability, elastic and electronic properties of a novel BN2 sheet with extended hexagons with N–N bonds. (6th March 2018) - Waters, Kevin; Pandey, Ravindra
Abstract: A new B–N monolayer material (BN2 ) consisting of a network of extended hexagons is predicted using density functional theory. The distinguishable nature of this 2D material is found to be the presence of the bonded N atoms (N–N) in the lattice. Analysis of the phonon dispersion curves show this phase of BN2 to be stable. The calculated elastic properties exhibit anisotropic mechanical properties that surpass graphene in the armchair direction. The BN2 monolayer is metallic with in-plane p states dominating the Fermi level. Novel applications resulting from a strong anisotropic mechanical strength together with the metallic properties of the BN2 sheet with the extended hexagons with N–N bonds may enable future innovation at the nanoscale.